The post-black and post-white church becoming the beloved community in a multi-ethnic world - Smith, Efrem (Efrem D.), 1969- (Jossey-Bass leadership network series, 2012)
"A blueprint for missional, multi-ethnic Christian communityEfrem Smith, an internationally recognized and innovative African-American leader, offers a workable plan for connecting theology, practical ministry models, and real stories of people in multi-ethnic Christian communities. Using the example of Jesus, Smith develops a theology of multi-ethnic and missional leadership. Embracing urban and ethnic subcultures such as hip-hop, this book provides a rich mix of multi-ethnic church development, reconciliation theology, missional church thinking, and Christian community. Provides a common-sense approach to creating a multi-ethnic Christian community Includes practical ministry models and real stories of people who are members of thriving multi-ethnic congregations Author is acclaimed African-American thought leader who planted and led a multi-ethnic churches of close to 1,000 and now leads a regional division of a denominational committed to ethnic, multi-ethnic, and missional churches This book is written for anyone wrestling with what it means to be a Christian in an increasingly multi-ethnic world polarized by class, politics, and race"--